Pengaruh Variasi Intensitas dan Aktivitas Instruktur Terhadap Kebugaran Jasmani Instruktur Eristy Management Semarang (Universitas Negeri Semarang, 2021)
The background of the problem that underlies this research is the effect of variations in intensity and activity of instructors on Eristy Management Semarang. The purpose of this study was to determine the relationship between variations in activity and instructor intensity on physical fitness EM Sekar Prima This study uses quantitative research with a correlational approach, the intention is to determine whether there is a relationship between two or more variables. The data collection technique used a questionnaire survey method The results of the study p = 0.014 and the value of r = 0.542, it can be interpreted that there is a significant relationship between intensity variations and physical fitness. And for the instructor's activity on physical fitness, the p value = 0.090 and the r value = 0.389, it can be interpreted that there is no significant relationship between the instructor's activity on physical fitness.. The conclusions of this study are 1) There is a relationship between intensity variations on the physical fitness of aerobic exercise instructors with a correlation coefficient of 0.014 with a significance value of 0.542. 2) There is no relationship between instructor activity and physical fitness with a correlation coefficient of 0.090 with a significance value of 0.389. 3) There is a relationship between intensity variations, activity on physical fitness of aerobic gymnastics instructors with a correlation coefficient that affects physical fitness with a value of 34.8% or significant.